Apremilast monotherapy in DMARD-naive psoriatic arthritis patients: results of the randomized, placebo-controlled PALACE 4 trial. (4th April 2018) - Wells, Alvin F; Edwards, Christopher J; Kivitz, Alan J; Bird, Paul; Nguyen, Dianne; Paris, Maria; Teng, Lichen; Aelion, Jacob A
Abstract: Objectives: The PALACE 4 trial evaluated apremilast monotherapy in patients with active PsA who were DMARD-naive. Methods: Eligible patients were randomized (1:1:1) to placebo, apremilast 20 mg twice a day or apremilast 30 mg twice a day. At week 16 or 24, placebo patients were rerandomized to apremilast. Double-blind apremilast treatment continued to week 52, with extension up to 4 years. The primary endpoint was the proportion of patients achieving ⩾20% improvement in ACR response criteria (ACR20) at week 16; secondary endpoints included the mean change in the HAQ Disability Index (HAQ-DI) score at week 16. Results: A total of 527 patients with mean disease duration of 3.4 years and high disease activity were randomized and received treatment. More apremilast patients achieved ACR20 response at week 16 [placebo, 15.9%; 20 mg, 28.0% ( P = 0.0062); 30 mg, 30.7% ( P = 0.0010)]. The mean HAQ-DI improvements were −0.17 (20 mg; P = 0.0008) and −0.21 (30 mg; P < 0.0001) vs 0.03 (placebo). Both apremilast doses showed significant ACR50 responses vs placebo at week 16 and improvements in secondary efficacy measures (swollen/tender joint counts) and psoriasis assessments, with sustained improvements through week 52. Common adverse events (AEs) over 52 weeks were diarrhoea, nausea, headache and upper respiratory tract infection; most events were mild or moderate. Serious AEs and AEs leading to discontinuation were comparable between groups. Laboratory abnormalities were infrequent and transient. Conclusions: In DMARD-naive patients, apremilast monotherapy improved PsA signs/symptoms over 52 weeks and was generally well tolerated. Trial registration: ClinicalTrials.gov (http://clinicaltrials.gov ), NCT01307423.